1975
DOI: 10.1136/pgmj.51.592.53
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses to selective β-adrenergic stimulation in man

Abstract: SummaryThe responses of plasma free fatty acid, glucose, lactate, insulin and growth hormone to intravenous administration of the predominantly P-2 stimulant, salbutamol, were studied in nine normal subjects. Four subjects received the predominantly 1-1 blocking agent, practolol, together with salbutamol.Salbutamol produced a marked rise in free fatty acid levels and there was also an appreciable increase in insulin values; lactate levels rose moderately and glucose values increased slightly; growth hormone le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(42 citation statements)
references
References 16 publications
(9 reference statements)
2
40
0
Order By: Relevance
“…heart and adipose tissue as fil. However, a considerable number of reports indicate that there are differences between the pharmacological characteristics of cardiac and adipose tissue fiadrenoceptors, both in animals and in man (Harms, Zaagsma & van der Wal, 1974;Goldberg, Joffe, Bersohn, Van As, Krut & Seftel, 1975;Gibbons et al, 1975;Harms, 1976b). Comparison of the antagonist potencies of several cardioselective P-adrenoceptor blocking agents on human cardiac, bronchial and adipocyte fl-adrenoceptors against isoprenaline induced effects (Harms & van der Meer, 1975;Harms, 1976a) also suggests that these agents are somewhat less effective in blocking adipocyte fl-adrenoceptors than cardiac,B-adrenoceptors.…”
Section: Plasma Renin Activitymentioning
confidence: 99%
“…heart and adipose tissue as fil. However, a considerable number of reports indicate that there are differences between the pharmacological characteristics of cardiac and adipose tissue fiadrenoceptors, both in animals and in man (Harms, Zaagsma & van der Wal, 1974;Goldberg, Joffe, Bersohn, Van As, Krut & Seftel, 1975;Gibbons et al, 1975;Harms, 1976b). Comparison of the antagonist potencies of several cardioselective P-adrenoceptor blocking agents on human cardiac, bronchial and adipocyte fl-adrenoceptors against isoprenaline induced effects (Harms & van der Meer, 1975;Harms, 1976a) also suggests that these agents are somewhat less effective in blocking adipocyte fl-adrenoceptors than cardiac,B-adrenoceptors.…”
Section: Plasma Renin Activitymentioning
confidence: 99%
“…Low doses of the P2-adrenoceptor selective agonist salbutamol were found to have an almost specific effect on plasma free fatty acids (Goldberg et al, 1975); nonselective antagonists, like propranolol and pindolol are more potent than cardioselective agents such as metoprolol in blocking catecholamineinduced increases in plasma free fatty acids, not only on a mg for mg basis, but also relative to their cardiac (pl) effects. The relatively weak antilipolytic effect of cardioselective 3-adrenoceptor blocking agents has been found in studies using either isoprenaline or adrenaline as the agonist and was also reported in a study using exercise induced sympathetic activation as the agonist (Harms et al, 1978;William-Olsson et al, 1979;Lundborg et al, 1981;Raptis et al, 1981).…”
Section: Studies In Manmentioning
confidence: 99%
“…Increased glycogenolysis in the liver and skeletal muscle results in hyperglycaemia and hyperlactataemia (Kuo, Kamaka & Lum, 1977). Increased lipolysis in adipose tissue shown by Goldberg, Van As, Joffe, Krut, Bersohn & Seftel (1975), increases plasma free fatty acid and ketone concentrations. Hyperglycaemia and direct stimulation of pancreatic 1 cells (Day, 1975) cause insulin release.…”
Section: Introductionmentioning
confidence: 99%